Sequence and Series: An Analysis of Mathematical Problem Solving Ability - Maryati, Iyam; Fadhilah, Dila Nurhayati (IndoMath: Indonesia Mathematics Education, 2021)
This study aims to analyze the level of mathematical problem solving abilities of students in one of the high schools in Garut City on the material of sequence and series. The method used in this research is descriptive qualitative research method. The sample in this study was conducted on 5 students in class XI at one of the public high schools in Garut City. The instruments given to the students were 4 questions on the sequence and series material. The conclusion of this study is the mathematical problem solving ability of class XI high school students in Garut City, seen from the indicators of identifying sufficient data to solve problems and implementing strategies to solve problems, is quite high, but the indicators of making mathematical models are classified as moderate, and checking the correctness of results and answers still relatively low.